2007
DOI: 10.1002/pts.778
|View full text |Cite
|
Sign up to set email alerts
|

Size does matter: further studies in hand–pack interaction using computer simulation

Abstract: This study expands on a previous work by the authors where it was shown through the use of ethnography and finite element models that a link exists between the choice of grip and joint stresses. Further finite element models are created to investigate the relationship between joint stresses and hand dimensions. This is an important area of research for inclusive design, since some of the most vulnerable members of society, such as elderly women, often exhibit extremes of physical dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
(3 reference statements)
0
15
1
Order By: Relevance
“…Designers strive to gain more insight into the opening process with the aim of making it easy for most users. Different analysis tools for packaging design have recently come into wide use, including finite element analysis, mathematical modeling, and Monte‐Carlo simulation . Practically, an efficient package can be achieved through understanding user requirements that can be used as guidelines to assess package performance .…”
Section: Package Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…Designers strive to gain more insight into the opening process with the aim of making it easy for most users. Different analysis tools for packaging design have recently come into wide use, including finite element analysis, mathematical modeling, and Monte‐Carlo simulation . Practically, an efficient package can be achieved through understanding user requirements that can be used as guidelines to assess package performance .…”
Section: Package Openingmentioning
confidence: 99%
“…Yoxall et al, 158 Hensler et al, 159 Lin et al, 160 and Yoxall and Rowson 161 It is important to consider the user and package performance. Yoxall et al, 162,165 Han et al, 164 and…”
Section: Packaging Designmentioning
confidence: 99%
“…For example, Han et al have investigated that the relationship between tab ring shape and the feelings in the fingertip when opening aluminum beverage cans; and they have concluded that the tab with a larger contact area with finger is better 1 . Openability of the bottle caps, which is one of a demand of aluminum beverage bottles for consumers' satisfaction, has been studied by some researchers [2][3][4][5][6][7] . However, these researchers have not determined the optimum opening diameter that is easy to open.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a package must contain information required by law, such as nutritional content and net weight and to maximize its convenience or utility functions, it should be simple to hold, open, use, and (if appropriate) reclose by the consumer (Yoxall et al, 2007). A range of variables influence packaging developments.…”
Section: Human Environmentmentioning
confidence: 99%
“…This is the environment in which the package is handled by people, and designing packages for this environment requires knowledge of the strengths and frailties of human vision, human strength and weakness, dexterity, memory, cognitive behavior, and so on (Yoxall et al, 2007). For example, a package must contain information required by law, such as nutritional content and net weight and to maximize its convenience or utility functions, it should be simple to hold, open, use, and (if appropriate) reclose by the consumer (Yoxall et al, 2007).…”
Section: Human Environmentmentioning
confidence: 99%